Optimizing Performance of a 4 kW BLDC Motor in Go-Kart Through Load and Speed Testing - Hesti Hermawati; Darwin Rio Budi Syaka; Rani Anggrainy (Fakultas Teknik Universitas Pancasila, 2026)
The development of electric go-karts involves overcoming challenges related to efficiency across different driving conditions. A key issue is the reduction in efficiency caused by changes in speed and the driver’s weight, both of which impact the motor’s power demands. This study focuses on examining how variations in driver weight (55 kg, 65 kg, and 75 kg) and speed (40 km/h, 50 km/h, and 60 km/h) affect the efficiency of a 4 kW BLDC motor in an electric go-kart. The research employed a quantitative experimental approach, conducting field tests on a 300-meter flat track. Key data, including voltage, current, and torque, were measured to calculate the motor’s input and output power, with efficiency determined by the power ratio formula. Analysis using a Two-Way ANOVA test revealed that both driver weight and speed, as well as their interaction, had a significant effect on efficiency (p<0.001). The highest efficiency recorded was 95.45% at 55 kg and 40 km/h, while the lowest was 62.49% at 75 kg and 60 km/h. These findings align with previous research, confirming that increased load and speed decrease efficiency. Such insights can guide strategies to optimize electric vehicle performance.